Clinical researchThe value of ultrasonography in the detection of renal scarring after urinary tract infection in children: preliminary results - Niafar, Farid; Seyedzadeh, Abolhassan; Hamedani, Sedighe A; Hamidi, Sepehr (Archives of Medical Science, 2007)
Introduction: There is controversy whether ultrasonography (US) can be reliably used to diagnose renal scars in children following pyelonephritis. This study aimed to assess the value of US in detecting renal scars using 99mTc-dimercaptosuccinic acid (DMSA) scintigraphy as the reference diagnostic test. Material and methods: In a prospective setting, 62 children who had been diagnosed as having pyelonephritis were studied. All children were evaluated with DMSA scintigraphy and US, each performed by one examiner. The interval between DMSA scanning and US was at most 2 days. A radiologist recorded his findings for each kidney as scarred or unscarred based on established criteria. The sensitivity of US relative to DMSA scintigraphy in the detection of renal scarring was calculated. Results: The study subjects were 20 boys and 42 girls, with a median age of 15 months (range, 2 months-6 years). Twenty-nine children were reported to have renal scarring on DMSA scintigraphy, of whom 12 (41.4%) were correctly diagnosed as having renal scars on US. The sensitivity of US in detecting scarred kidneys was 36.8%, and its specificity 97.7%. The sensitivity of US in detecting kidneys with multiple scars was higher than kidneys with a single scar (p=0.007). The development of renal scarring was not related to gender (p=0.3). Increasing age was associated with developing renal scars with an odds ratio of 1.53 for each year increase in age after adjustment for sex. Conclusions: The results of this preliminary study show that US cannot be used reliably as the sole imaging method for detecting pediatric renal scarring.